2016
DOI: 10.1038/bjc.2016.19
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic interactions of autophagy with radiation and temozolomide in glioblastoma: evidence and issues to resolve

Abstract: Glioblastoma is a unique model of non-metastasising disease that kills the vast majority of patients through local growth, despite surgery and local irradiation. Glioblastoma cells are resistant to apoptotic stimuli, and their death occurs through autophagy. This review aims to critically present our knowledge regarding the autophagic response of glioblastoma cells to radiation and temozolomide (TMZ) and to delineate eventual research directions to follow, in the quest of improving the curability of this incur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 117 publications
2
57
0
Order By: Relevance
“…Regarding the response to treatment, the results presented in this study agree with a review study 25 , which found a relationship between TMZ + RT therapy combination and an increase in survival in patients with glioma 7,8 .…”
supporting
confidence: 90%
“…Regarding the response to treatment, the results presented in this study agree with a review study 25 , which found a relationship between TMZ + RT therapy combination and an increase in survival in patients with glioma 7,8 .…”
supporting
confidence: 90%
“…Yao et al [14] found that irradiation of human glioma cells led to increased autophagy. Another study [15] showed that the induction of autophagy by radiotherapy resulted in radioresistance of glioblastoma. However, little research has concentrated on the relationship between autophagy and radioresistance of bladder cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike low-grade gliomas, the complete surgical removal of glioblastoma is impossible due to the infiltrative nature of the disease and functional vulnerability of the brain [6]. Postoperative radiotherapy with the administration of temozolomide (TMZ) and local delivery of ACNU could remove most of the residual glioma cells, but not glioma stem cells.…”
Section: Introductionmentioning
confidence: 99%